Menjelajahi Solusi Inovatif Logistik Bisnis Kuliner - Tuwuh Adhistyo Wijoyo; Julian Andriani Putri; Fransiska Ayu Aprilia; Salsabila Febriani Putri (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia's economy with a contribution of around 60% to the Gross Domestic Product and the absorption of more than 90% of the national workforce. In the culinary sector, MSMEs face various challenges, especially in terms of limited access to technology, efficient logistics management, and the implementation of hygiene practices that meet standards. This community service activity aims to empower culinary MSMEs through a structured and comprehensive approach that includes technology training, managerial capacity building, and the implementation of food safety standards. The method of implementing activities consists of three main stages: (1) preparation and planning, (2) implementation of training and mentoring, and (3) evaluation and follow-up. The training is focused on the use of digital technology for business operations, financial and logistics management, and hygiene practices in food production. Mentoring is carried out intensively to ensure that knowledge and skills transfer is effective. The results of the activity showed a significant increase in the understanding and skills of culinary MSME actors. Partners are able to adopt simple technology to support business operations, improve management systems, and implement better hygiene practices. In addition, this activity succeeded in building a collaborative network between MSMEs, academics, local governments, and the private sector, which strengthened the local business ecosystem. However, challenges in the form of limited financial resources and the need for ongoing assistance are still major concerns. Overall, this program makes a real contribution to increasing the competitiveness of culinary MSMEs, encouraging local economic growth, and supporting the development of an inclusive and sustainable business ecosystem based on community empowerment.